2010
DOI: 10.1016/j.taap.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory effects of inhaled sulfur mustard in rat lung

Abstract: Inhalation of sulfur mustard (SM), a bifunctional alkylating agent that causes severe lung damage, is a significant threat to both military and civilian populations. The mechanisms mediating its cytotoxic effects are unknown and were investigated in the present studies. Male rats Crl:CD(SD) were anesthetized, and then intratracheally intubated and exposed to 0.7–1.4 mg/kg SM by vapor inhalation. Animals were euthanized 6, 24, 48 h or 7 days post-exposure and bronchoalveolar lavage fluid (BAL) and lung tissue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
124
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 66 publications
12
124
0
Order By: Relevance
“…SM-induced oxidative stress is thought to be a primary event triggering inflammation [16,32]. In our study, oxidant-antioxidant imbalance due to changes in GSH and MDA levels in moderate and severe groups may lead to progressive inflammation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…SM-induced oxidative stress is thought to be a primary event triggering inflammation [16,32]. In our study, oxidant-antioxidant imbalance due to changes in GSH and MDA levels in moderate and severe groups may lead to progressive inflammation.…”
Section: Discussionmentioning
confidence: 56%
“…MDA levels in the sputum and exhaled breath condensate and plasma of patients with different pulmonary diseases have been reported to be in the range of controls [31] or elevated compared to healthy controls [6]. Similarly, the MDA level was increased in BAL of patients with SM-induced pulmonary injury [8,32].…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 is the most important type of MMP involved in SM toxicity. Previous studies have indicated that MMP9 status rises following SM injury (Calvet et al 1999;Malaviya et al 2010). In the current research, immunotherapy with IFNg was associated with a remarkable decline in serum MMP9; this effect may prevent deleterious consequences of protease activation by SM.…”
Section: Discussionmentioning
confidence: 96%
“…were selected to determine if antioxidant treatments would affect their presence in bronchoalveolar lavage fluid (BALF) (Emmler et al, 2007;Malaviya et al, 2010;Ricketts et al, 2000;Seagrave et al, 2010;Zhu et al, 2014). The cytokines were analyzed using a proinflammatory multiplex panel that included cytokines previously reported to be elevated by SM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Adult male Sprague Dawley rats (200-300 g) from Charles River Laboratories (Wilmington, Massachusetts) were used. Animals were exposed to SM or vehicle (ethanol, EtOH) at the USAMRICD Aberdeen Proving Ground using a vapor generator based model as previously reported (Anderson et al, 1996(Anderson et al, , 2000(Anderson et al, , 2009;Gao et al, 2011;Malaviya et al, 2010;Veress et al, 2015). Rats were anesthetized with a combination of ketamine (80 mg/ kg, IM) and xylazine (10 mg/kg, IM).…”
Section: Methodsmentioning
confidence: 99%